The preparticipation sports examination - Hergenroeder, A. C. (Pediatric Clinics of North America, 1997)
Approximately 5.5 million high school students participated in high school sports in the United States during 1991 and 1992.1 and 12 The American Medical Association (AMA) Guidelines for Adolescent Preventive Services (GAPS) recommends that a comprehensive health evaluation occur at least every other year during the adolescent period. In addition, the American Academy of Pediatrics recommends that adolescents involved in strenuous activity have a sports-specific examination on entry into junior and senior high school and that such an examination be updated by an annual questionnaire emphasizing recent injuries or any health condition affecting sports participation. The student must have annual physician clearance to continue participating, which requires the physician reviewing an updated health history and performing the directed physical examination discussed later. The preparticipation sports examination (PSE) is not a comprehensive health maintenance visit because topics such as drug use, sexual activity, violence, mental health, and immunizations are not routinely addressed; however, the PSE is used as a substitute for the annual comprehensive health evaluation for 30% to 78% of adolescents.7 and 11 Some parents expect psychosocial issues to be addressed and immunizations to be given. The role of the PSE, then, is and has been controversial regarding its goal. If it is a comprehensive examination, then more than what is described here needs to be done.14 This discussion of the PSE assumes that the athlete is receiving regular maintenance care, and the PSE is in addition to their routine care. If the PSE is the athlete's only encounter with the health care system, then the physician should decide what conditions will be screened for and how follow-up of the screening tests will be arranged. Mechanisms wherein teens receive annual comprehensive health maintenance visits and have PSEs should be a priority, although the current trend in managed care to limit medical expenditures (e.g., physician time) argues against this priority.